2007
DOI: 10.1214/07-sts227d
|View full text |Cite
|
Sign up to set email alerts
|

Comment: Performance of Double-Robust Estimators When “Inverse Probability” Weights Are Highly Variable

Abstract: We thank the editor Ed George for the opportunity to discuss the paper by Kang and Schaeffer.The authors' paper provides a review of doublerobust (equivalently, double-protected) estimators of (i) the mean µ = E(Y ) of a response Y when Y is missing at random (MAR) (but not completely at random) and of (ii) the average treatment effect in an observational study under the assumption of strong ignorability. In our discussion we will depart from the notation in Kang and Schaeffer (throughout, K&S) and use capital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
361
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(370 citation statements)
references
References 12 publications
7
361
1
1
Order By: Relevance
“…Previous examples of Proposition 12 are given in Newey (1990, p. 116), Newey (1999, and Robins et. al.…”
Section: Vector Of Instrumental Variables Andλmentioning
confidence: 97%
“…Previous examples of Proposition 12 are given in Newey (1990, p. 116), Newey (1999, and Robins et. al.…”
Section: Vector Of Instrumental Variables Andλmentioning
confidence: 97%
“…The second models, incorrectly specified, were as the first ones, but with covariate X instead of L. In the second experiment, as in Robins et al (2007), we recoded A as 1 − A and replicated the first experiment. We conducted this experiment because Robins et al (2007) noted that the favourable performance ofβ reg (η) compared withβ(η,α) reported by Kang & Schafer (2007) was reversed when the observed data were {1 − A, (1 − A)Y, L}; thus, our study includes scenarios favourable toβ reg (η) and tô β (η,α).…”
Section: Simulation Studiesmentioning
confidence: 99%
“…Several authors (Robins & Wang, 2000;Kang & Schafer, 2007;Rubin & van der Laan, 2008) have noted that standard double-robust estimators may have substantial bias and large variance, even under correct specification of the missingness model, if the estimated missingness probabilities are highly variable and/or the outcome regression model is misspecified. Alternative double-robust estimators have been recently developed to address these problems (van der Laan & Rubin, 2006;Tan, 2006Tan, , 2007Tan, , 2008Tan, , 2010aTan, , 2010bRobins et al, 2007;Cao et al, 2009). In particular, Tan (2008Tan ( , 2010a and Cao et al (2009) derived double-robust estimators of E(Y ) = β 0 , i.e., in the special case in which Z is absent and h(Z ; β) = β, which satisfy Properties 1 and 2 and have the enhanced efficiency benefit that:…”
Section: Introductionmentioning
confidence: 99%
“…It is known that when both models are correct, then the inference is an expected one. Also, it is known that when both models are incorrect, the estimates are severely biased and lead to an incorrect inference [22]. Finally, the impact of ignoring the left-censoring of the outcome was examined by replacing censored values either by half of the lower limit of detection or by a randomly imputed value with the models a WMM h and a WMM r , respectively.…”
Section: Simulation Study For Non-ignorable Missing and Left-censoredmentioning
confidence: 99%